38th Winter School on Vibroacoustical Hazards Suppressions - Roman BUKOWSKI (Archives of Acoustics, 2013)
Traditionally I invite you to acquaint with some abstracts of lectures submitted to presentation in 38th Winter School on Vibroacoustical Hazards Suppressions. This national School, organized by Upper Silesian Division of the Polish Acoustical Society and Institute of Physics at Silesian University of Technology, at this year is planned at the first week of March 2010. This conference is organized in different places of Silesian Beskidy Mountains, but this year it is organized in Szczyrk. The conference is the forum for all environmental vibroacoustics fields. Particularly it concern to traffic noise, industry noise, vibroacoustics of machines, room acoustics, noise protection and similar problems. During the School the theoretical works, experimental, measuring, technical, applied and normative ones are presented. The School lectures, and other conference materials, will be published in the "Materials of the XXXVIII Winter School on Vibroacoustical Hazards Suppressions" (in Polish) edited by Dr. Roman Bukowski and Dr. Mieczysław Roczniak (chairman of the conference). This publication is intend to participants of the School and for many libraries in Poland. Other information about XXXVIII WS on VHS you can find at address: http://ogpta.polsl.pl/szzzw